Chemical composition, antibacterial and antioxidant activities of essential oils extracted from dry and fresh Brocchia cinerea (Vis.) - Nisrine Chlif; Abdelaziz Ed-Dra; Mohammed Diouri; Noureddine El Messaoudi; Badr Zekkori; Fouria Rhazi Filali; Amar Bentayeb (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Chlif N, Ed-Dra A, Diouri M, Messaoudi NE, Zekkori B, Filali FR, Bentayeb A. 2021. Chemical composition, antibacterial and antioxidant activities of essential oils extracted from dry and fresh Brocchia cinerea. Biodiversitas 22: 1741-1749. Brocchia cinerea Vis. is a medicinal plant belonging to the Asteraceae family, widely used in traditional medicine and as a food condiment by southeast Moroccan populations. This study aimed to determine the chemical composition of essential oils (EOs) of fresh and dry aerial parts of B. cinerea and to evaluate their antibacterial and antioxidant activities. Chemical composition was determined by GC-MS and antibacterial activity was performed against six pathogenic bacteria. Moreover, the antioxidant activity was evaluated by ferric reduction antioxidant power and DPPH scavenging assay. The main components of fresh plants were thujone (26.05%), cis-chrysanthenyl formate (15.64%), 2-champhanone (15.40%), and santolina-triene (10.68%). Whereas, the major components of the dry plant were thujone (22.37%), santolina-triene (16.45%), 1,8-cineol (12.19%), and chrysanthenyl formate (12.03%). The EOs exert a bactericidal effect against both Gram-positive and Gram-negative bacteria. However, the antioxidant assays showed that EOs of fresh and dry aerial parts of B. cinerea could reduce iron and trap DPPH radical. In a nutshell, this study showed that the EOs of fresh and dry aerial parts of B. cinerea are rich in natural substances that had interesting biological activities and can be used in the medical, pharmaceutical, and agri-food sectors.